Analisis Desain Interior Pada Restoran Warung Suluh - Nanda Reisya Violetta; Rizki Ramdhani (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This study aims to analyze the interior design that attracts consumers in the suluh stall restaurant and also to describe the menu that is the best seller in this restaurant. The analysis method used is the descriptive method., by finding enough detailed information in several references. The restaurant itself not only sells the taste of a dish, but restoran also sells a comfortable atmosphere for consumers. Various innovations have sprung up because the culinary business competes to keep up with the development of the world. The café or restaurant that innovates by carrying out the concept of traditional and modern themes. This warung suluh restaurant presents a traditional nuance concept. The theory of this research is Interior design is the process of compiling and creating various interior elements so that they can become a related unit in order to achieve certain goals in the aspects of aesthetics, comfort and safety of the room (THABRONI). The result of this study is to explain the design of the warung suluh restaurant carrying the concept of old Jogja which has a variety of classic interiors.